An uncommon case of fibrolipoma - Ahanthem Nandita Devi; M B Sowbhagya; P Balaji; T S Mahesh Kumar (Wolters Kluwer Medknow Publications, 2017)
Lipoma is a common benign soft-tissue neoplasm derived from mature adipose tissue neoplasm, but its presence in the oral and pharyngeal region is relatively uncommon. Oral lipoma was first described by Roux in 1848 as "yellow epulis." It has an incidence rate of about 1%-4% of all benign oral lesions, with a prevalence rate of about 0.0002%. Fibrolipoma is an extremely rare subtype of lipoma which accounts for 1.6% of all facial lipomas. Specific anatomic locations of occurrence within the oral and maxillofacial region include the parotid region, buccal mucosa, lips, submandibular region, tongue, floor of mouth, and palate. Here, we present fibrolipoma, a very rare subtype of lipoma involving the left retromolar region in a 50-year-old female patient.